A questionnaire technique for assessing the stress at work - Hladký, A (Journal of hygiene, epidemiology, microbiology, and immunology, 1984)
Subjective perception of the stress at work is a phenomenon reflecting the experience-mediated relationship between the sum of objective conditions of work and the sum of individual's traits available to cope with demands of the work environment. This relationship is mirrored in the function of the whole organism and can be described using the formula S = f (E, D), where S = the state of the organism, E = exposure (i.e. the sum of all stressors the organism is exposed to), and D = disposition (i.e. the sum of traits the organism has available to cope with these stressors). Based on these theoretical considerations, a questionnaire has been developed as a tool for assessing the work stress in different groups of occupations. This "Work Stress Assessment" (WSA) questionnaire was used in a group of 4800 female employees from various branches of the printing industry. Of a total of 160 questionnaire items, 98 items were selected and used to assess the workload in these employees, using a 5-point rating scale of evaluation. The responses were processed statistically, separately for 3531 blue-collar and 1269 white-collar respondents. The use of the factor analysis method revealed that the two groups of jobs had 16 factors in common, 3 factors were specific for blue-collar and 2 factors for white-collar jobs. Judged by factor components, the responses of subjects were well structured and the perceived stress at work turned out to well reflect the reality of conditions of work, which confirms the construct validity of this methodical approach based on the subjective perception of occupational stress. High coefficients of consistency (0.959 for blue-collar and 0.946 for white-collar occupations) point to the reliability of this questionnaire technique. Thus, the WSA questionnaire appears to suitably complement the other methodical approaches aimed at assessing the stress at work in different groups of occupations.
Keywords: ženské pohlaví; Female; Work Schedule Tolerance; Stress, Physiological; Work; Job Satisfaction; pracovní uspokojení; lidé; fyziologický stres; dospělí; vliv směnného provozu na zdraví; Humans; průzkumy a dotazníky; Surveys and Questionnaires; Adult; práce